EFEKTIVITAS KERJA APARAT DESA (STUDI KASUS DI DESA PAKUUE DUA KECAMATAN TENGA KABUPATEN MINAHASA SELATAN) - RAMPI, JOHANES; RURU, JOORIE MARHAEN; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2020)
This research is done for the purpose of explaining the effectiveness of village personnel in the village of Pakuure two Tenga district of South Minahasa Regency in the study of public administration. The study uses qualitative approach methods. The subject of this study amounted to 10 of the one occupying the research site so researchers took the conclusion to give the Kuisoner to the 10 subjects. . Data collection using interviews, observations, behavioral studies (documentation), while the analytical techniques used are qualitative data analysis interaction models Miles and Huberman and Sugiono. The results of the study showed (a) more productivity is realized in the implementation of non-physical development and less attention to the empowerment and strengthening of economic potential of the village community. (b) The creativity of the village apparatus is formed in establishing a working relationship with the district and district governments as well as in conjunction with religious leaders but lack creativity in presenting the government program to Improving people’s living standards. (c) The working intensity of the village apparatus is manifested in the division of work and seeks to optimally serve the community. However, the intensity of work produced as a form of occupational effectiveness has not been followed by the involvement and support of the community. Keywords: effectiveness, work effectiveness, village apparatus